Universal properties of highly frustrated quantum magnets in strong magnetic fields - Derzhko, Oleg; Richter, Johannes; Honecker, Andreas; Schmidt, Heinz-Jürgen (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
The purpose of the present paper is two-fold. On the one hand, we review some recent studies on the low-temperature strong-field thermodynamic properties of frustrated quantum spin antiferromagnets which admit the so-called localized-magnon eigenstates. One the other hand, we provide some complementary new results. We focus on the linear independence of the localized-magnon states, the estimation of their degeneracy with the help of auxiliary classical lattice–gas models and the analysis of the contribution of these states to thermodynamics.